Randomized phase II trial of lymphodepletion plus adoptive cell transfer of tumor-infiltrating lymphocytes, with or without dendritic cell vaccination, in patients with metastatic melanoma. Issue 5 (21st May 2021) - Saberian, Chantal; Amaria, Rodabe N.; Najjar, Amer M.; Radvanyi, Laszlo G.; Haymaker, Cara L.; Forget, Marie-Andrée; Bassett, Roland L.; Faria, Silvana C.; Glitza, Isabella C.; Alvarez, Enrique; Parshottam, Sapna; Prieto, Victor; et al.
Abstract : Background: The adoptive transfer of tumor-infiltrating lymphocytes (TIL) has demonstrated robust efficacy in metastatic melanoma patients. Tumor antigen–loaded dendritic cells (DCs) are believed to optimally activate antigen-specific T lymphocytes. We hypothesized that the combined transfer of TIL, containing a melanoma antigen recognized by T cells 1 (MART-1) specific population, with MART-1-pulsed DC will result in enhanced proliferation and prolonged survival of transferred MART-1 specific T cells in vivo ultimately leading to improved clinical responses. Design: We tested the combination of TIL and DC in a phase II clinical trial of patients with advanced stage IV melanoma. HLA-A0201 patients whose early TIL cultures demonstrated reactivity to MART-1 peptide were randomly assigned to receive TIL alone or TIL +DC pulsed with MART-1 peptide. The primary endpoint was to evaluate the persistence of MART-1 TIL in the two arms. Secondary endpoints were to evaluate clinical response and survival. Results: Ten patients were given TIL alone while eight patients received TIL+DC vaccine. Infused MART-1 reactive CD8 + TIL were tracked in the blood over time by flow cytometry and results show good persistence in both arms, with no difference in the persistence of MART-1 between the two arms. The objective response rate was 30% (3/10) in the TIL arm and 50% (4/8) in the TIL+DC arm. All treatments were well tolerated. Conclusions: The combination of TIL +DC showed no difference in the persistence of MART-1 TIL compared with TIL therapy alone. Although more patients showed a clinical response to TIL+DC therapy, this study was not powered to resolve differences between groups. Trial registration number: NCT00338377 .